An Estimation Method of Metal‐Ligand Orbital Mixing in Lanthanide(III) Complexes Using Magnetic Circular Dichroism. Issue 9 (6th March 2018) - Kitagawa, Yuichi; Nakanishi, Takayuki; Fushimi, Koji; Hasegawa, Yasuchika
Abstract: The photophysical properties of lanthanide(III) complexes depend on the magnitude of orbital mixing between the lanthanide(III) and ligands. Herein, an estimation method of orbital mixing in lanthanide(III) complexes is reported using LnCl3 ⋅ n H2 O (Ln=Pr, Gd, Tb) and Ln(tfa)3 (H2 O)2 (tfa: trifluoroacetylacetonate, Ln=Pr, Gd, and Tb) for the first time. The electronic state properties were assessed from the electronic absorption and magnetic circular dichroism (MCD) spectra. The MCD spectra revealed the energy levels of the spin‐allowed and spin‐forbidden 4 f–5d transitions of the Tb(III) complex that is hidden by the intense π–π* transition of the ligands. This energy gap corresponds to the exchange splitting energy between the 5d and 4f n−1 electrons, which provides information regarding the orbital mixing between the Tb(III) ion and the ligands. Abstract : Magnetic circular dichroism can reveal the energy level of the spin‐allowed and spin‐forbidden 4 f–5d transition bands of lanthanide(III) complexes that are hidden by the intense π‐π* transition band. This energy gap provides information regarding the mixing of the 5d and ligand orbitals, which provides a new approach for understanding the photophysical properties of lanthanide(III) complexes.